Over a Century Evidence of Historical and Recent Dryness/ Wetness in Sub-Humid Areas: A Uganda, East African Case - Byakatonda, Jimmy; Openy, Geoffrey; Sempewo, Jotham Ivan; Mucunguzi, Dominic Banaga (Meteorological Applications, 2021)
Many regions globally are grappling with the challenge of recurrent extreme weather events. Whereas attempts are being undertaken to understand their characteristics as a first step to guide targeted mitigation measures, these are focused on dryness and not wetness, which is also a challenge in sub-humid areas. This study investigates dryness and wetness characteristics using the standardized precipitation evaporation index (SPEI) at timescales of 3, 6, 12 and 24 months for a period of 1901–2018 across Uganda's drainage basins. Trends in the dryness and wetness evolutions were conducted using the Mann-Kendall (MK) statistic to establish the effects of global warming on the study area. A step change analysis reveals 1961 as a change point year from cool to warm periods. Results also reveal that warming mainly occurred in the recent period (1962–2018), with a temperature rise of over 2οC being recorded in 2009. Severe dryness events occurred in the recent period as opposed to wetness events that dominated the earlier period (1901–1961). Dryness and wetness varied among drainage basins, with the Aswa basin being more susceptible to severe dryness while the Lake Kyoga basin to severe wetness. Lira and Kitgum were identified as drought hotspots at timescales of 3, 6 and 12 months. SPEI was able to reveal 60% of historical dryness events and 75% of wetness events on record, making it an adequate tool for monitoring humid events as opposed to droughts in sub-humid climates. It is hoped that this evidence can guide targeted mitigation measures towards climatic shocks within the region.
Keywords: climate variability, disaster risk, drought hotspot, drought severity, global warming, standardized precipitation evaporation index